PENGGUNAAN PERKEMBANGAN APLIKASI FACEBOOK BAGI REMAJA DI DESA TINIAWANGKO MINAHASA SELATAN - Jessica Lidya Sumolang; Z. H Singal; Y.D.A Santie (Labor Program Studi Pendidikan Sosiologi, 2021)
The purpose of this research is to analyze and describe how the use of facebook application development for teenagers in Tiniawangko village, south minahasa. The research method used is qualitative. Qualitative research methods aim to provide a systematic, factual and accurate description. Data collection techniques are observation, interviews and documentation. The results of research in the field show that the use of Facebook application development for teenagers in Tiniawangko village is very important because it can help teenagers to add insight, knowledge, interact, be creative and can also find out the latest information and can communicate with friends and family